2019
DOI: 10.21276/ijcmr.2019.6.12.33
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Burden of Carbapenem-Resistant Pseudomonas aeruginosa and Acinetobacter baumannii Infections in a Tertiary Care Hospital of Eastern India

Abstract: Introduction: Healthcare associated infections(HAI) by multi-drug resistant organisms(MDRO) are major cause of mortality and morbidity having significant impact on quality of life and economic burden. HAI by carbapenem-resistant Pseudomonas aeruginosa (CRPsA) and Acinetobacter baumannii (CRAB) are emerging threat for their high antibiotic resistance and spread via mobile genetic elements. Objectives of this study were to detect prevalence of CRPsA and CRAB infections in a tertiary care hospital of Eastern Indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 13 publications
6
2
0
Order By: Relevance
“…In a tertiary care facility in Delhi, Wattal et al reported high carbapenem resistance in Enterobacterales, with a prevalence ranging from 13% to 51%. 17 In our study, the prevalence of CRAB (9.84%) and CRPA (3.16%) which is similar to previous studies by Grewal et al 18 and Bandyopadhyay et al 19 According to Benachinmardi, et al, 20 P. aeruginosa infections were more common, indicating a recent trend towards an increase in A. baumannii infections.…”
Section: Discussionsupporting
confidence: 90%
“…In a tertiary care facility in Delhi, Wattal et al reported high carbapenem resistance in Enterobacterales, with a prevalence ranging from 13% to 51%. 17 In our study, the prevalence of CRAB (9.84%) and CRPA (3.16%) which is similar to previous studies by Grewal et al 18 and Bandyopadhyay et al 19 According to Benachinmardi, et al, 20 P. aeruginosa infections were more common, indicating a recent trend towards an increase in A. baumannii infections.…”
Section: Discussionsupporting
confidence: 90%
“…38 A. baumannii was predominantly isolated from blood samples (5.2%) followed by sputum (2.1%), wounds (2.1%) and urine (1%) in the present study. This study corroborated a study from India at a tertiary care hospital, 45 and from Madagascar. 7 However; the finding of the…”
Section: Discussionsupporting
confidence: 88%
“…28 On the other hand, it was lower than a study from Ethiopia, 27 United States, 26 and Latin America. 46 The proportion of carbapenem resistant P. aeruginosa isolates in the present study is consistent with studies done in Egypt, 42 India, 45 and United States. 26 However, it was higher than a study from Ethiopia 27 and Libya (24%).…”
supporting
confidence: 91%
See 2 more Smart Citations